The Involvement of Corin in the Progression of Diabetic Erectile Dysfunction in a Rat Model by Down‐Regulating ANP /NO/cGMP Signal Pathway. Issue 8 (25th April 2017) - Wang, Jian; Mi, Yuanyuan; Yuan, Fenglai; Wu, Sheng; You, Xiaoming; Dai, Feng; Huang, Yi; Cao, Jia; Zhu, Jin; Xue, Boxin; Zhu, Lijie
ABSTRACT: This study was aimed to analyze the potential role of Corin in the procession of diabetic ED and to explore the underlying mechanism. Diabetic ED rat model was constructed and the characteristics of diabetic ED and control rats were recorded at 4, 8, 12, and 16 weeks. qRT‐PCR and Western bloting were used to detected the mRNA and protein levels. Intracellular cGMP detection was accomplished using a commercial radioimmunoassay method. Vascular endothelial cell from rat corpus cavernosum spiral artery was isolated and transfected with si‐ Corin to analyzed the potential role of Corin. Cell viability was assessed using crystal violet. The results showed that diabetic ED rats showed significantly higher glucose level, and lower body weight, ICP level, and ICP/MAP ratio at 12 and 16 weeks in diabetic ED rats compared with control rats. The protein levels of Corin, atrial natriuretic peptide (ANP) and eNOS, and the level of cGMP were significantly down‐regulated in corpus cavernosum in diabetic ED rats, revealing the potential role of Corin in NO‐associated diabetic ED. Further, studies proved that defect of Corin not only inhibited the vascular endothelial cell viability in high‐glucose condition, but also suppressed ANP, eNOS, and cGMP expression in vascular endothelial cells. To sum up, Corin contributes to the progression of diabetic ED and the underlying mechanism is associated with the down‐regulation of ANP /NO/cGMP signal pathway. J. Cell. Biochem. 118: 2325–2332, 2017. © 2017 Wiley Periodicals, Inc. Abstract : This is the first evidence demonstrating that the Corin is a contributing factor to the progression of diabetic ED. The underlying mechanism is associated with the down‐regulation of ANP/NO/cGMP signal pathway. The study also indicates that Corin can be used as a new therapeutic strategy for diabetic ED.